2005
DOI: 10.1016/j.jpainsymman.2005.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Late Referral to Hospice and Bereaved Family Member Perception of Quality of End-of-Life Care

Abstract: The Family Evaluation of Hospice Services was used to document bereaved family members' perceptions of whether their loved ones were referred too late to hospice and to examine the association of that perception and quality of end-of-life care. A mortality follow-back survey of bereaved family members from two not-for-profit hospices found that 13.7% of decedents were referred at a time too late for hospice services. Family members of persons referred too late reported lower satisfaction with hospice services,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 38 publications
4
94
1
Order By: Relevance
“…Similar conclusions have been made in a number of studies addressing barriers to palliative care access [13][14][15] , and programs such as Living Lessons have been set up to increase public awareness of palliative care 16 . Schockett et al found that late referral to end-of-life care, such as to outpatient hospice in the United States, was positively associated with lower patient and family satisfaction with care 14 . This preliminary indication of reduced benefit, which may also apply to palliative care in Canada, supports the preparation programs mentioned earlier.…”
Section: Discussionsupporting
confidence: 65%
“…Similar conclusions have been made in a number of studies addressing barriers to palliative care access [13][14][15] , and programs such as Living Lessons have been set up to increase public awareness of palliative care 16 . Schockett et al found that late referral to end-of-life care, such as to outpatient hospice in the United States, was positively associated with lower patient and family satisfaction with care 14 . This preliminary indication of reduced benefit, which may also apply to palliative care in Canada, supports the preparation programs mentioned earlier.…”
Section: Discussionsupporting
confidence: 65%
“…17 Late referrals to hospice correlate with lower overall family satisfaction, lower satisfaction with hospice services, more unmet needs, lack of awareness about what to expect at time of death, lower confidence in participating in patient care at home, and more concerns about coordination of care. 18 In half of all cases of late referral, family members reported that physicians were a barrier to earlier hospice referral. 19 It can be difficult to determine when to transition from nonhospice palliative care to hospice, and this should be a group decision made among patient, family members, and healthcare providers.…”
Section: Relationship Of Nonhospice Palliative Care To Hospice Palliamentioning
confidence: 99%
“…3,4 In addition, earlier hospice enrollment may provide added benefits of increased family satisfaction and greater cost savings. 5,6 Despite the potential benefits of early hospice enrollment, many patients with cancer are admitted to hospice close to the end of life. In 2012, for instance, the median length of stay in hospice in the United States was only 18.7 days.…”
Section: Introductionmentioning
confidence: 99%